Single nucleotide polymorphism analysis in interstitial cystitis/painful bladder syndrome - Cassão, Valter D.; Reis, Sabrina T.; Pimenta, Ruan; Lucon, Marcos; Leite, Katia R. M.; Srougi, Miguel; Bruschini, Homero (PloS one, 2019)
Interstitial Cystitis (IC) is a chronic condition diagnosed based on the presence of symptoms, such as suprapubic/ pelvic pain, pressure or discomfort in association with urgency and increased urinary frequency. Confusable diseases must be excluded. However, there is no objective test or marker to establish the presence of the disease. Diagnosis and patient management is often difficult, given the poor understanding of IC pathogenesis and its unknown etiology and genetics. As an attempt to find biomarkers related to IC, we assessed the association between 20 selected single nucleotide polymorphism (SNPs) with IC and pain severity. To assess the presence of SNPs in IC patients' blood samples and correlate them with the disease and chronic pain condition. A case-control study was conducted. We selected 34 female patients with IC diagnosed according to NIDDK criteria and 23 patients in the control group (previously healthy women with only stress urinary incontinence). IC patients were allocated into two groups according to reported chronic pain severity. We selected the following SNPs for analysis: rs1800871, rs1800872, rs1800896, rs1800471, rs1800629, rs361525, rs1800497, rs6311, rs6277, rs6276, rs6313, rs2835859, rs11127292, rs2243248, rs6887695, rs3212227, rs1799971, rs12579350, rs3813034, and rs6746030. Genotyping was performed by real-time PCR (q-PCR). The polymorphic allele of SNP rs11127292 exhibited a higher frequency in subjects with IC than in controls (p:0.01). The polymorphic allele of SNP rs6311 was more frequent in patients with severe pain (p:0.03). The frequency of the wild-type allele of SNP rs1799971 was higher in patients with mild to moderate pain (p:0.04). The results indicated differences in SNP frequency among subjects, suggesting that SNPs could serve either as a marker of IC or as a marker of pain severity in IC patients. The study showed promising results regarding IC and polymorphism associations. These associations have not been previously reported.